Model Manajemen Komunikasi Sosial Kodam XVI Pattimura - Nur, Nisa Atin; Kaliky, Pahrul Idham (Jurnal Ilmu Komunikasi Pattimura, 2023)
ABSTRACT : The Indonesian National Army (TNI) is an instrument of the state in charge of maintaining and protecting state security. Currently the threat of division through negative issues is spreading on social media so it needs to be addressed. TNI also has a dark history in the New Order era, so that reforms continue to be carried out to win the hearts and minds of the people. The number of cases involving elements of the TNI has made the community re-equalize the TNI as before. Social communication is an important element that must be done in overcoming these problems. The purpose of this study was to determine the social communication management of KODAM XVI Pattimura. The theory used is communication management and S-O-R by using qualitative research methods. Data collection techniques used are in-depth interviews and direct observation. The results obtained are: social communication management KODAM XVI Pattimura using the POAC management function and the Matouscha doll management model consisting of self, interpersonal, system and competence. It can be concluded that the management of social communication has an effect on changes in people's attitudes and perceptions. So that it can be said effective even though it still has drawbacks. Keywords: Social Communication Management, Matouscha Doll, POAC Management Function